Energetics of a Solar Flare and a Coronal Mass Ejection Generated by a Hot Channel Eruption - Qingmin Zhang; Weilin Teng; Dong Li; Jun Dai; Yanjie Zhang (The Astrophysical Journal, 2023)
Hot channels (HCs) are prevalent in the solar corona and play a critical role in driving flares and coronal mass ejections (CMEs). In this paper, we estimate the energy content of an X1.4 eruptive flare with a fast CME generated by an HC eruption on 2011 September 22. Originating from NOAA Active Region 11302, the HC is the most dramatic feature in 131 and 94 Å images observed by the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO). The flare is simultaneously observed by SDO/AIA, the Reuven Ramaty High-energy Solar Spectroscopic Imager, and the Extreme-ultraviolet Imager on board the “behind” Solar Terrestrial Relations Observatory (STEREO). The CME is simultaneously detected by the white-light coronagraphs of the Large Angle Spectroscopic Coronagraph on board the Solar and Heliospheric Observatory and the COR1 coronagraph on board the behind STEREO. Using multiwavelength and multiview observations of the eruption, various energy components of the HC, flare, and CME are calculated. The thermal and kinetic energies of the HC are (1.77 ± 0.61) × 10 ^30 erg and (2.90 ± 0.79) × 10 ^30 erg, respectively. The peak thermal energy of the flare and total radiative loss of the soft X-ray–emitting plasma are (1.63 ± 0.04) × 10 ^31 erg and (1.03–1.31) × 10 ^31 erg, respectively. The ratio between the thermal energies of the HC and flare is 0.11 ± 0.03, suggesting that the thermal energy of the HC is not negligible. The kinetic and potential energies of the CME are (3.43 ± 0.94) × 10 ^31 erg and (2.66 ± 0.49) × 10 ^30 erg, yielding a total energy of (3.69 ± 0.98) × 10 ^31 erg for the CME. Continuous heating of the HC is required to balance the rapid cooling by heat conduction, which probably originates from intermittent magnetic reconnection at the flare current sheet. Our investigation may provide insight into the buildup, release, and conversion of energies in large-scale solar eruptions.